DEMOPLOT BUDIDAYA PISANG DI KWT RUKUN TANI DESA ADI WARNO KECAMATAN BATANG HARI LAMPUNG TIMUR - Jamaludin, Jamaludin; Krisnarini, Krisnarini; Puji Handayani, Etik; Rakhmiati, Rakhmiati (Jurnal Pengabdian Nasional, 2022)
Yards are generally planted with various types of plants, ranging from high crown plants to low crownplants. However, choosing the wrong types of plants actually makes land use not optimal because notall plants planted can produce. Banana is a commodity that is widely grown around the house and inmixed gardens. The existence of vacant land in the yard of the KWT Rukun Tani member's house, AdiWarno Village, Batang Hari District, East Lampung Regency has the potential to be planted withbananas. Although some members have planted bananas in their yards, their growth and productivityis still low due to limited knowledge and skills in banana cultivation. The purpose of community serviceactivities is to transfer knowledge from tertiary institutions (service teams) to the community (KWTRukun Tani), through counseling activities and banana cultivation demonstration plots for the use ofyard land and increasing the income of KWT members. Based on the activities that have been carriedout, members of KWT Rukun Tani feel that the service activities carried out are very useful becausethey get new knowledge about good and correct banana cultivation. Currently the bananas planted indemonstration plots, in the yard and in the collective garden, are growing very well and some of theplants have started to bear fruit.